ATHE ACTIVITIES OF THE POLICE IN ENSURING THE CONSTITUTIONAL RIGHTS AND FREEDOMS OF CITIZENS - Anna Yu Aslanova (Современная наука и инновации, 2022)
This article discusses the constitutional rights and freedoms of citizens as objects of policing.